Pediatric hereditary angioedema: an update [version 1; referees: 2 approved] - Geetika Sabharwal (F1000Research, 2017)
Hereditary angioedema (HAE) with C1-inhibitor (C1-Inh) deficiency (C1-Inh-HAE) is a rare, life-threatening, and disabling genetic disorder characterized by self-limited tissue swelling caused by deficiency or dysfunction of C1-Inh. Our aim in this update is to discuss new advances in HAE therapy, focusing mainly on the various treatment options that have become available recently and also drugs that are under trial for prophylaxis to prevent attacks. There is a paradigm shift to where the treatment of HAE is headed, focusing now on prophylactic treatment rather than abortive management.